2011
DOI: 10.5423/ppj.2011.27.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Efficacies of Bacillus Species Against Cylindrocarpon destructans Causing Ginseng Root Rot

Abstract: Two antifungal bacteria were selected from forest soils during the screening of microorganisms antagonistic to Cylindrocarpon destructans, a cause of ginseng root rot. The antifungal bacteria were identified as Bacillus subtilis (I4) and B. amyloliquefaciens (yD16) based on physiological and cultural characteristics, the Biolog program, and 16S rRNA gene sequencing analyses. Antagonistic activity of both bacterial isolates to C. destructans increased with increasing temperature. More rapid starch hydrolytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
2
14
0
2
Order By: Relevance
“…Many studies have demonstrated PGPEs to be effective biocontrol agents for plant protection in vitro and in vivo and field application of suspensions of Bacillus spp. in the growth season of plants more over resulted in significantly reduced disease incidence [1,9,14,19]. PGPEs are rhizosphere bacteria that can enhance plant growth in a wide variety of applications such as microbial pesticides, microbial fertilizers, and animal feed additives.…”
Section: B Mojavensis Kjs-3 As a Pgpementioning
confidence: 99%
“…Many studies have demonstrated PGPEs to be effective biocontrol agents for plant protection in vitro and in vivo and field application of suspensions of Bacillus spp. in the growth season of plants more over resulted in significantly reduced disease incidence [1,9,14,19]. PGPEs are rhizosphere bacteria that can enhance plant growth in a wide variety of applications such as microbial pesticides, microbial fertilizers, and animal feed additives.…”
Section: B Mojavensis Kjs-3 As a Pgpementioning
confidence: 99%
“…Members of the genus Bacillus are known to suppress various plant diseases, such as anthracnose in red peppers [3] , mangos and wax apples [4] , as well as root rot in ginseng caused by Fusarium cf. incarnatum and Cylindrocarpon destructans [5,6] . Furthermore, Bacillus subtilis has been reported to be relatively benign to humans and several B. subtilis strains are listed by the Organic Materials Review Institute [7] .…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is expensive for soil-borne disease, and the effects of chemicals diminish over time as it takes at least 4 years before ginseng is harvested. Alternatively, a biological strategy has been widely performed; several Bacillus strains were shown to have a highly antagonistic effect against C. destructans [ 8 ]. However, in most tests aimed at confirming the efficacies of such biological agents, only the inhibition levels of mycelial growth have been measured, and not inhibition of chlamydospore germination.…”
mentioning
confidence: 99%